The DK science encyclopedia. - DK Publishing, Inc. (New York : DK Pub., 1998)
A comprehensive guide to science and technology, arranged by such topics as matter, weather, and living things.
Includes index.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
5.9.
5.9
Keywords: Science -- Encyclopedias, Juvenile; Science -- Encyclopedias; Science -- Encyclopedias